2003
DOI: 10.1007/bf02416930
|View full text |Cite
|
Sign up to set email alerts
|

Use of simulated bioterrorist attacks to evaluate syndromic surveillance systems based on multiple data sources

Abstract: i136POSTER ABSTRACTS duction in specificity or incidence will reduce the PVP and raise the ratio of FP to TP; a reduction in sensitivity will also reduce the PVP. Efforts to improve the sensitivity and specificity of the screening method can increase PVP, but as long as incidence is low, the ratio of FP to TP will be high. There is a reticence to evaluate syndromic surveillance systems, which may be warranted. If the system has never experienced a TP, quantitative evaluation results are known in advance. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, combining surveillance populations provides a larger statistical sample of total population in the region for earlier recognition of disease events and monitoring the spread of a communicable disease through a community. Prior evaluations of biosurveillance systems with multiple data streams found that data from different sources was useful for detecting and monitoring disease outbreaks and provide a substantial alerting-timeliness advantage [ 19 - 21 ]. ESSENCE has previously been linked with disparate systems for real-time data exchange and communication [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, combining surveillance populations provides a larger statistical sample of total population in the region for earlier recognition of disease events and monitoring the spread of a communicable disease through a community. Prior evaluations of biosurveillance systems with multiple data streams found that data from different sources was useful for detecting and monitoring disease outbreaks and provide a substantial alerting-timeliness advantage [ 19 - 21 ]. ESSENCE has previously been linked with disparate systems for real-time data exchange and communication [ 22 ].…”
Section: Introductionmentioning
confidence: 99%